2024
DOI: 10.1039/d3ta05951k
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the stability challenges of TiOx-based passivating contacts for high-efficiency c-Si solar cells

Mohamed M. Shehata,
Thien N. Truong,
Gabriel Bartholazzi
et al.

Abstract: Our research unveils strategies for developing exceptional TiOx-based passivating contacts, potentially replacing traditional Si-based ones with highly stable, transparent alternatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Although the introduction of a TCO layer helps reduce ρ c by preventing the formation of AgO, its impact on the passivation quality should be considered. Several studies have indicated that sputtering TCO can cause damage to the underlying layers, , thereby degrading the passivation quality. Shehata et al demonstrated that introducing an ALD-deposited ZnO layer with a thickness of 3 nm as a buffer layer before sputtering ITO helps prevent permanent sputtering damage and maintains the passivation quality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the introduction of a TCO layer helps reduce ρ c by preventing the formation of AgO, its impact on the passivation quality should be considered. Several studies have indicated that sputtering TCO can cause damage to the underlying layers, , thereby degrading the passivation quality. Shehata et al demonstrated that introducing an ALD-deposited ZnO layer with a thickness of 3 nm as a buffer layer before sputtering ITO helps prevent permanent sputtering damage and maintains the passivation quality.…”
Section: Resultsmentioning
confidence: 99%
“…To maintain the passivation quality of TiO x -based contacts during metallization, recent studies have proposed effective solutions to this issue. Shehata et al 57 introduced an ALD-deposited ZnO buffer layer to mitigate the damage caused by metallization. They reported that a ZnO buffer layer, when sufficiently thick (13 nm or more), effectively prevents degradation resulting from metallization, thereby improving the stability and overall performance of the TiO x -based contacts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation